The Failure of the ‘Playing Victim’ Strategy in Gaining Support: A Study of the 2024 Presidential Election in Indonesia - Rofiq, Rofiq; Agus, Agus Supratikno (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
This article explains the depictions of candidate figures in the 2024 presidential election. The aim of this study is to find out how to portray presidential candidates as victims who are persecuted by the cruelty of the authorities who side with the candidate team of Prabowo Subianto and Gibran Rakabuming Raka. The important question raised in this research is why the scenario of becoming a victim needs to be carried out. The main reason is because the team of Anis Rasyid Baswedan and Muhaimin Iskandar, as well as Ganjar Pranowo and Mahfudz MD did not receive support from President Jokowi. So, to get help from the voters, these two teams created a scenario of becoming victims, in order to get electoral support. In this research, we chose to use a qualitative method with a case study approach with the aim of being able to see and hear more closely the various election experiences in Indonesia, especially after the collapse of the New Order regime. The focus of the study is directed at constructing how to gain electoral support in the face of non-neutrality of government officials, politicization of social assistance, engineering of legal rules, and politicization in other forms which result in creating a backlash to gain sympathy from voters in the election. This article specifically discusses the dynamics of the 2024 presidential election in Indonesia.